Trends in the burden of gastroesophageal reflux disease in China and Global from 1990 to 2021 and predictive analysis for 2040 - Zexu Tang; Zelin Chen; Yongjian Huang; Jinwen Fang; Xiangyang Yang; Chunzhu Li; Huiying Zhang; E. Xie (PLoS ONE, 2026)
Background This study analyzed the temporal trends in the age- and gender-specific disease burden of gastroesophageal reflux disease (GERD) in China from 1990 to 2021, comparing its incidence, prevalence, and disability-adjusted life years (DALYs) with global estimates. Methods Data were extracted from the Global Burden of Disease (GBD) database 1990–2021. The Joinpoint regression model was used to quantify trends via annual average percentage change (AAPC) and 95% confidence intervals. Multidimensional comparisons were conducted by age, gender, and time. Results From 1990 to 2021, China exhibited declining trends in age-standardized incidence, prevalence, and DALYs rates for GERD, in contrast to increasing trends globally. Disease burden was higher among females and increased with age, with the middle-aged and elderly experiencing the greatest rise. Projections indicate a continued increase in GERD burden in China by 2040. Conclusion Despite recent declines, GERD remains a significant public health challenge in China due to its large population and rapid aging. Targeted prevention and intervention strategies are urgently needed.